Description of a new species of Odontofroggatia (Chalcidoidea, Epichrysomallinae) associated with Ficus microcarpa (Moraceae) with a key to species of the genus - Feng, Gui; Huang, Da-Wei (Zootaxa, 2010)
Odontofroggatia is a non-pollinating fig wasp genus associated with a narrow range of host species (Ficus microcarpa and F. prasinicarpa). A new species, Odontofroggatia quinifuniculus Feng & Huang sp. nov., is described from specimens reared from F. microcarpa in Hainan province, China. A key for distinguishing species is presented. The holotype is deposited in Institute of Zoology, Chinese Academy of Sciences.